Development Of The 2022 Pencak Silat Pull Training Model Using Resistance Bands In The Pre-Competition Phase - Muhammad, Ihyaudin; Rahayuni, Kurniati; Widiawati, Prisca (UNIB Press, 2025)
Changes to the pencak silat rules in 2022 have had a significant impact on techniques in sparring category pencak silat matches, namely the fall technique with a pull. However, to fulfill the demands of the task when playing, the need for adjustments to techniques during training is the key to the success of techniques when playing. Therefore, researchers are interested in developing a variation of the fall technique model with a pull. The purpose of this research is to develop a variation of the pull training model using resistance bands to support techniques in addressing the 2022 pencak silat regulations. This research uses the Research and Development (R&D) method. The results of this study are 11 variations of the pull training model with resistance bands. The results of the martial arts expert validation were 90% declared excellent, meaning that it is feasible to be applied in pre-competition phase training activities. The results of the respondent test in the small group trial showed 90% in the excellent category and the large group trial showed 91% categorized as excellent. The results of the product validity test were declared feasible to use.